Preimage security evaluations on Rijndael-based hashing: a comprehensive study - Zhang, Tianyu (Nanyang Technological University, 2023)
The Meet-in-the-Middle (MITM) attack is one of the most powerful cryptanalysis techniques, as seen by its use in preimage attacks on MD4, MD5, Tiger, HAVAL, and Haraka-512 v2 hash functions and key recovery for full-round KTANTAN. An efficient approach to constructing MITM attacks is automation, which refers to engraving MITM propagation characteristics into an optimization model and searching for the optimal configuration using optimizers. Our work focuses on the simplification and renovation of the most advanced superposition framework based on Mixed-Integer Linear Programming (MILP) proposed by Bao et al. in CRYPTO 2022. With our refined model, we provide the first comprehensive study of the preimage security of hash functions based on the Rijndael block cipher family, versions of which are chosen to be the Advanced Encryption Standard (AES) by NIST in 2001, and improve the best known results. Specifically, we have extended the attack rounds of Rijndael 256-192 and 256-192, reduced the attack complexity of Rijndael 256-128 and 128-192 (AES192), and filled the void of preimage security evaluation on Rijndael specifications with a 192-bit block size. In addition, a generic framework of quantum MITM attacks is given to extend our accomplishments in the classical setting to quantum.